2008
DOI: 10.1007/s12010-008-8145-z
|View full text |Cite
|
Sign up to set email alerts
|

A New Lipase Isolated from Oleaginous Seeds from Pachira aquatica (Bombacaceae)

Abstract: A new lipase from seeds of Pachira aquatica was purified to homogeneity by SDS-PAGE obtaining an enzyme with a molecular weight of approximately 55 kDa. The purified lipase exhibited maximum activity at 40 degrees C and pH 8.0, for an incubation time of 90 min. Concerning temperature stability, at the range from 4 to 50 degrees C, it retained approximately 47% of its original activity for 3 h. The enzyme activity increased in the presence of Ca(++) and Mg(++), but was inhibited by Hg(++), Mn(++), Zn(++), Al(++… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 33 publications
6
19
0
3
Order By: Relevance
“…Nevertheless, recently, seed lipases have been the focus of increasing attention as biocatalysts. In some cases, these enzymes present advantages over animal and microbial lipases due to some very interesting features such as specificity, low cost, availability, and easily purification, representing a great alternative for potential commercial use as industrial enzymes [46]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, recently, seed lipases have been the focus of increasing attention as biocatalysts. In some cases, these enzymes present advantages over animal and microbial lipases due to some very interesting features such as specificity, low cost, availability, and easily purification, representing a great alternative for potential commercial use as industrial enzymes [46]. …”
Section: Introductionmentioning
confidence: 99%
“…However, their single biggest market is detergent formulations. The functional importance of lipases in detergent industries is to remove fatty residues in laundry and dishwashers, for cleaning clogged drains, and for avoiding pipes' clogging [4, 1921]. Some studies have been done adding lipases to detergent formulations or adding these detergents to lipase assays to evaluate enzyme stability [4, 9, 20].…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Cetto e Heinrich (2005), o consumo de Pachira aquática aublet pode ter efeito hipoglicemiante no tratamento de diabetes e seus sintomas. em estudos realizados por Polizelli et al (2008) e Lago et al (1987) foram constatados elevado teor de óleo (44,1%) no fruto de Pachira aquática aublet, sendo o ácido palmítico o seu principal componente. Polizelli et al (2008) também observaram elevado teor de triptofano, aminoácido precursor de um importante neurotransmissor, a serotonina.…”
Section: Introductionunclassified
“…em estudos realizados por Polizelli et al (2008) e Lago et al (1987) foram constatados elevado teor de óleo (44,1%) no fruto de Pachira aquática aublet, sendo o ácido palmítico o seu principal componente. Polizelli et al (2008) também observaram elevado teor de triptofano, aminoácido precursor de um importante neurotransmissor, a serotonina. oliveira et al (2000), estudando a composição e as propriedades nutricionais de sementes, encontraram teores de 53,9% de óleo e 12,9% de proteínas.…”
Section: Introductionunclassified
“…During germination and cotyledon senescence, oil bodies are degraded by lipases, which mobilize stored TAGs (Vijayakumar and Gowda, 2012). It has been reported that, with a few exceptions, lipase activity is absent in ungerminated (or dormant) seeds and increases rapidly upon germination (e.g., Peres Polizelli et al, 2008). In some cases, enzymes isolated from dormant seeds -for example from castor bean (Estamond, 2004), peanut (Sanders and Pattee, 1975), or Jatropha curcas (Abigor et al, 2002) -are highly active in vitro but apparently inactive in vivo.…”
Section: Reverse Transcription (Rt)-pcrmentioning
confidence: 99%